Analisis Teknikal Saham Menggunakan Indikator RSI dan Bollinger Bands pada Saham Konstruksi - Revo Gilang Firdaus (Jurnal Pasar Modal dan Bisnis, 2021)
Modern technical analysis research is becoming increasingly popular today, such as the Relative Strength Index and the Bollinger Bands. The research objective was conducted to determine the results of the combination of RSI and BB on construction stocks. The research method was carried out by selecting construction stocks through purposive sampling of four stocks which then applied the RSI and BB indicators. Then the analysis is carried out by looking at the momentum of the combination of the RSI and BB in determining buy and sell. The results showed that the combination of RSI and BB is quite accurate in determining whether to buy or sell, as evidenced by the reflection of the price when it hits the bottom and top of the RSI and BB indicators. Meanwhile, the implication of this research is that investors can determine buying and selling of shares using a combination of RSI and BB indicators and can provide a reference for analysts, both in securities and MI, to provide recommendations forcustomers